Anisotropic Polymer Adsorption on Molybdenite Basal and Edge Surfaces and Interaction Mechanism With Air Bubbles - Xie, Lei; Wang, Jingyi; Huang, Jun; Cui, Xin; Wang, Xiaogang; Liu, Qingxia; Zhang, Hao; Liu, Qi; Zeng, Hongbo (Frontiers in Chemistry, 2018)
The anisotropic surface characteristics and interaction mechanisms of molybdenite (MoS2) basal and edge planes have attracted much research interest in many interfacial processes such as froth flotation. In this work, the adsorption of a polymer depressant [i.e., carboxymethyl cellulose (CMC)] on both MoS2 basal and edge surfaces as well as their interaction mechanisms with air bubbles have been characterized by atomic force microscope (AFM) imaging and quantitative force measurements. AFM imaging showed that the polymer coverage on the basal plane increased with elevating polymer concentration, with the formation of a compact polymer layer at 100 ppm CMC; however, the polymer adsorption was much weaker on the edge plane. The anisotropy in polymer adsorption on MoS2 basal and edge surfaces coincided with water contact angle results. Direct force measurements using CMC functionalized AFM tips revealed that the adhesion on the basal plane was about an order of magnitude higher than that on the edge plane, supporting the anisotropic CMC adsorption behaviors. Such adhesion difference could be attributed to their difference in surface hydrophobicity and surface charge, with weakened hydrophobic attraction and strengthened electrostatic repulsion between the polymers and edge plane. Force measurements using a bubble probe AFM showed that air bubble could attach to the basal plane during approach, which could be effectively inhibited after polymer adsorption. The edge surface, due to the negligible polymer adsorption, showed similar interaction behaviors with air bubbles before and after polymer treatment. This work provides useful information on the adsorption of polymers on MoS2 basal/edge surfaces as well as their interaction mechanism with air bubbles at the nanoscale, with implications for the design and development of effective polymer additives to mediate the bubble attachment on solid particles with anisotropic surface properties in mineral flotation and other engineering processes.